Adaptation - Plotz, John; Vadde, Aarthi; Perrotta, Tom; Wollaeger, Mark (Brandeis University, 2021)
Novelist, screenwriter, and HBO showrunner Tom Perrotta joins his old friend Mark Wollaeger (who also happens to be a top scholar of modernism) for a wide-ranging conversation about literature, television, and everything in between. Tom reveals that he has been reading a most peculiar self-help book: Richard Ellmann's biography of James Joyce. Mark then shares some juicy Joyce anecdotes before getting into the nitty gritty of style and craft. We discuss balancing difficult themes with accessible prose and debate whether a therapeutic model of novel-writing (where characters grow and change) can translate into a therapeutic model of culture (where social and political norms can grow and change). Speaking of growing and changing, adaptation is at the center of this episode as we revisit Tom's amazing work on The Leftovers, Mrs. Fletcher, Little Children, and of course, Election.
Tom Perrotta and Mark Wollaeger Go from Page to Screen (AV)
Keywords: Literature